2023
DOI: 10.1007/s40620-023-01591-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, clinical characteristics and prognostic value of acute kidney injury in COVID-19 compared with influenza virus and respiratory syncytial virus

Abstract: Background Acute Kidney Injury (AKI) complicates a substantial part of patients with COVID-19. Direct viral penetration of renal cells through the Angiotensin Converting Enzyme 2 receptor, and indirect damage by the aberrant inflammatory response characteristic of COVID-19 are likely mechanisms. Nevertheless, other common respiratory viruses such as Influenza and Respiratory Syncytial Virus (RSV) are also associated with AKI. Methods We retrospectively compared the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…All studies were retrospective cohort studies. Five studies were conducted in the United States ( 18 , 19 , 21 , 23 , 24 ), two in China ( 27 , 29 ), one in France ( 20 ), one in Austria ( 22 ), one in Turkey ( 25 ), one in Israel ( 26 ), and one in Pakistan ( 28 ). Eight studies ( 18 , 19 , 22–24 , 26 , 28 , 29 ) reported data on general hospitalized patients, and four studies reported data on critically ill patients in ICUs ( 20 , 21 , 25 , 27 ) and patients with ARDS requiring veno-venous ECMO ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies were retrospective cohort studies. Five studies were conducted in the United States ( 18 , 19 , 21 , 23 , 24 ), two in China ( 27 , 29 ), one in France ( 20 ), one in Austria ( 22 ), one in Turkey ( 25 ), one in Israel ( 26 ), and one in Pakistan ( 28 ). Eight studies ( 18 , 19 , 22–24 , 26 , 28 , 29 ) reported data on general hospitalized patients, and four studies reported data on critically ill patients in ICUs ( 20 , 21 , 25 , 27 ) and patients with ARDS requiring veno-venous ECMO ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in the United States ( 18 , 19 , 21 , 23 , 24 ), two in China ( 27 , 29 ), one in France ( 20 ), one in Austria ( 22 ), one in Turkey ( 25 ), one in Israel ( 26 ), and one in Pakistan ( 28 ). Eight studies ( 18 , 19 , 22–24 , 26 , 28 , 29 ) reported data on general hospitalized patients, and four studies reported data on critically ill patients in ICUs ( 20 , 21 , 25 , 27 ) and patients with ARDS requiring veno-venous ECMO ( 20 ). Three studies ( 27–29 ) enrolled patients with H1N1 (subtype of influenza A), six studies ( 20–24 , 26 ) enrolled patients with type A or B influenza, while the other four studies ( 18 , 19 , 24 , 25 ) recruited influenza patients without mentioning the subtype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to demographic information, Table 1 [4][5][6][7][8][9][10][11][12] days; other-AKI, 6 [4][5][6][7][8][9][10][11][12] days; P < .001). The COVID-AKI group also had the largest weight loss at the time of discharge with a median (IQR) of −1.9 (−6.2 to 0.5) kg compared with −0.9 (−3.6 to 1.0) kg for the flu-AKI group and −0.4 (−3.9 to 1.7) kg for the other-AKI group.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…[1][2][3][4] Although similar incidence of AKI is reported for patients hospitalized with COVID-19 and other respiratory viral illnesses, such as influenza, 5 COVID-19 has been associated with more severe AKI, higher incident chronic kidney disease (CKD), and higher mortality. [6][7][8] COVID-19 has also been associated with a range of functionally limiting long-term sequelae, even among individuals not requiring hospitalization. 9 Therefore, in addition to the acute adverse effects of COVID-19 on kidney function, there is a growing concern for prolonged adverse effects.…”
mentioning
confidence: 99%